Prospect of Early Planting of Potato Seed Crop in Central India - SADAWARTI, M.J.; BHATNAGAR, A.; SINGH, S.P.; PANDEY, K.K. (Indian Journal of Hill Farming, 2015)
A field experiment was conducted to study the prospect of early planting (5th October) in relation to present planting time (20th October) with four popular cultivars viz. Kufri Lauvkar,Kufri Chandramukhi, Kufri Chipsona-1 and Kufri Sindhuri grown under Gwalior region of central India for seed production. Days to first emergence was delayed by 5 days in early planting (5th October) than normal planting (20th October). Significantly higher yield (28.73 t/ha) was recorded in normal planting (20th October) over early planting (5th October). Water use efficiency was significantly higher in normal planting (114.92 kg/ha-mm) over early planting (59.65 kg/ha-mm). Higher incidence of insect-vectors i.e. thrips and whiteflies and necrosisdisease were observed in 5th October planted crop than 20th October planted crop. Hence planting of potato as seed crop in Gwalior region of central India cannot be recommended before 20th October. It needs further refinement of planting date after the 20th October.